Pengaruh Kualitas Produk, Promosi, dan Desain terhadap Keputusan Pembelian Smartphone OPPO di Kecamatan Driyorejo Kabupaten Gresik - Faisal Iman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to test whether there is an influence between product quality, promotion and design on purchasing decisions. The population in this study were OPPO smartphone users in Driyorejo District, Gresik Regency. The number of samples in this study was 112 respondents. The sampling technique used the purposive sampling method. The research method used is a quantitative method with data sources in the form of primary data, namely questionnaires filled out by respondents via gfrom. The data was processed using SMART PLS by testing the inner model and outer model. The results of this study provide evidence that product quality and design influence purchasing decisions, while promotion does not influence purchasing decisions.